THE VARIOUS FACTORS THROUGH EMPLOYEE JOB SATISFACTION AND EMPLOYEE PERFORMANCE AT THE INDONESIA’S NATIONAL ZAKAT AGENCY (BAZNAS), BOGOR CITY - Samsuhardo, Romi; Sugiono, Edi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The Indonesia's National Zakat Agency (BAZNAS) is the only agency to collect or distribute zakat, alms and donations at the national level that is recognized by the State. Due to the heavy task of BAZNAS to achieve a goal in the Zakat Infaq and Shodaqoh Collection institution. Employee performance plays a very important role because employee performance also affects the success or failure of a Zakat collection process in Indonesia. This study aims to analyze the respective influences of various factors, as Compensation, Organizational Culture, and Organizational Motivation on Employees Job Satisfaction of the Indonesia's National Zakat Agency (BAZNAS), Bogor City. Then, analyze the respective influences of Compensation, Organizational Culture, Organizational Motivation, and Employees Job Satisfaction on Employees Performance of the Indonesia's National Zakat Agency (BAZNAS), Bogor City and also analyze the influence each of Compensation, Organizational Culture, and Organizational Motivation on Employee Performance through Employee Job Satisfaction of the Indonesia's National Zakat Agency (BAZNAS), Bogor City. This research is a kind of causality, also prominent as an explanatory study conducted to identify the extent and nature of causal relationships with quantitative analysis approach. The sample consists of 100 respondents selected using a questionnaire. Data analysis was conducted using Smart PLS 3.0. The results indicate that Compensation and Motivation have an insignificant effect on Job Satisfaction. However, Organizational Culture has a significant effect on Job Satisfaction. Additionally, stakeholder satisfaction significantly affects loyalty. Organizational Culture, Motivation, and Job Satisfaction have a significant impact on Performance, whereas Compensation does not have a significant impact. Compensation, Organizational Culture, and Motivation do not have a significant impact on Performance through Job Satisfaction. These conclusions can serve as a basis for improving the quality of human resource development at BAZNAS Bogor City. Keywords: Compensation, Organizational Culture, Employee Job Satisfaction, Employee Performance